2020
DOI: 10.3390/jcm9030683
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Bone Marrow-Derived Mesenchymal Stem Cell Therapy on Oxidative Stress Intensity in Minimally Conscious State Patients

Abstract: Neurological disorders, including minimally conscious state (MCS), may be associated with the presence of high concentrations of reactive oxygen species within the central nervous system. Regarding the documented role of mesenchymal stem cells (MSCs) in oxidative stress neutralization, the aim of this study is to evaluate the effect of bone marrow-derived MSC (BM-MSC) transplantation on selected markers of oxidative stress in MCS patients. Antioxidant capacity was measured in cerebrospinal fluid (CSF) and plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 107 publications
0
6
0
Order By: Relevance
“…These limitations also affect the clinical applications of stem cells. Therefore, catalytic activities of antioxidant enzymes have been studied for ameliorating ROS for stem cell‐based osteogenic differentiation, tissue regeneration, etc [19–22] . However, the reduced stability of enzymes and their sensitivity to in vivo conditions hinder their practical use.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…These limitations also affect the clinical applications of stem cells. Therefore, catalytic activities of antioxidant enzymes have been studied for ameliorating ROS for stem cell‐based osteogenic differentiation, tissue regeneration, etc [19–22] . However, the reduced stability of enzymes and their sensitivity to in vivo conditions hinder their practical use.…”
Section: Figurementioning
confidence: 99%
“…Therefore, catalytic activities of antioxidant enzymes have been studied for ameliorating ROS for stem cell-based osteogenic differentiation, tissue regeneration, etc. [19][20][21][22] However, the reduced stability of enzymes and their sensitivity to in vivo conditions hinder their practical use. To address this challenge, the development of antioxidant enzyme-based artificial enzymes that can efficiently scavenge ROS is necessary.…”
mentioning
confidence: 99%
“…Transferring mitochondria from MSCs to neurons impaired by oxidative stress may contribute to the preservation of posttraumatic neurons and restore their function. In addition, it has been shown that MSCs can mitigate the effects of oxidative stress in the central nervous system by changing the activity of ascorbic acid and catalase [ 82 ]. MSCs can also increase expression of the antiapoptotic gene, Bcl-2 , and decrease the level of superoxide anion, thereby protecting brain tissue [ 83 ].…”
Section: The Role Of Mscs In Treating Tbimentioning
confidence: 99%
“…Finally, at the beginning of 2020, a clinical study was published relating to the ability of MSCs in oxidative stress neutralization. It is hypothesized that autologous transplantation of BM-MSCs decreases the range of oxidative stress in patients in minimally conscious state (mCS) [174]. The aim of this study was to evaluate the effect of BM-MSC transplantation on selected markers of oxidative stress in mCS patients.…”
Section: Clinical Trials Approved By Local Ethics Committeesmentioning
confidence: 99%